Student Worksheet Static Fluid Material Based on Scientific Approach Using Giuded Inquiry Model - Supardi Supardi; Chandra Ertikanto; Posman Manurung (Universitas Sebelas Maret, 2017)
This Research and development goal is to produce Student Worksheet (SWS) static fluid material based on the scientific approach using guided inquiry learning model, which is easy, interesting, useful and effective. This research was conducted through seven stages, namely: pra-research and data collection stage, planning stage, pra-developing product stage, pra-test stage, revising design stage, product test stage, and revising product stage. The pra-study stage consists of a literature study and teacher and student assessment analysis in Al Kautsar Bandar Lampung high school. The developing stage is produces (SWS) static fluid material with scientific approaches based using guided inquiry learning model with well validated of design expert and well enough of the material expert. The product test stage had been held on the sample with random cluster sampling technique which XI.IPA-5 class as the experimental class and XI.IPA-4 class as the control class. The results of this study indicate that the developing result SWS s has the easy category, interesting, useful, and good enough effective with the N-gain 0.599.